DETERMINATION OF EDUCATION QUALITY AND GRADUATE QUALITY: FUNDING AND CURRICULUM MANAGEMENT ANALYSIS - Mahputriono Mahputriono (Dinasti International Journal of Management Science, 2022)
In this study, the author tries to raise the issue of the quality of education and the quality of graduates directly related to funding and curriculum management. In achieving the quality of education and the quality of good graduates, it is necessary to support adequate funding because the completeness of infrastructure facilities, teacher welfare, proper and comfortable education places are all inseparable from funding. Fund management is an activity related to how to obtain funds and how to use these funds for the benefit of educational institutions so that the educational goals that have been set can run effectively and efficiently. The concept of funding management is that all expenditures, both monetary and non-monetary, are an expression of the responsibility of all parties (ie society, parents and the government) for the development of education. In addition, education funding must be drawn from various sources for maintenance, stabilization and administrative arrangement so that education costs can be implemented effectively and efficiently. Furthermore, the educational curriculum also plays a very significant role, therefore the curriculum must be well planned, carried out with full responsibility and evaluated on an ongoing basis to be in accordance with the vision and mission of the educational institution. This article reviews the determination of education quality and Graduate Quality: Funding and Curriculum Management Analysis, a study of Human Resource Management literature. The purpose of writing the article is to build a hypothesis of the influence between variables to be used in further research. The results of this library research are that: 1) Funding Management affects the Quality of Education; 2) Curriculum affects the Quality of Education; 3) Funding Management affects the Quality of Graduates; 4) Curriculum influences the Quality of Graduates; and 5) Quality of Education affects the Quality of Graduates.